1997
DOI: 10.1164/ajrccm.155.2.9032185
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and hemodynamic effects of continuous positive airway pressure in left heart failure.

Abstract: The ventilatory and hemodynamic effects of continuous positive airway pressure (CPAP) delivered via a face mask (at 0, 5, and 10 cm H2O, and after a return to 0 cm H2O) were studied in nine patients with acute left heart failure (pulmonary artery occlusion pressure [PAOP] > or = 18 mm Hg, and cardiac index [CI] < or = 2.8 L/min/m2). CPAP at 10 cm H2O induced an improvement in lung compliance (60 +/- 10 ml/cm H2O to 87 +/- 20 ml/cm H2O, p < 0.05) and in lung and airway resistance (5.7 +/- 1.0 cm H2O/L/s to 3.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0
13

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(142 citation statements)
references
References 13 publications
3
126
0
13
Order By: Relevance
“…The individualized adjustments of the EPAP may have affected the results reported by this study, based on studies on the hemodynamic effects of continuous positive airway pressure (CPAP). Hence, a constant value of EPAP was maintained to prevent any event related to a reduction in the cardiac output [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The individualized adjustments of the EPAP may have affected the results reported by this study, based on studies on the hemodynamic effects of continuous positive airway pressure (CPAP). Hence, a constant value of EPAP was maintained to prevent any event related to a reduction in the cardiac output [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Lung compliance improves and lung resistance falls with CPAP reducing the work of breathing (WOB). 79 There is also a reduction in the intrathoracic pressure swings and respiratory rate, representing a fall in respiratory muscle effort and leading to reduced left ventricular transmural pressure. 80 It has been previously demonstrated that as WOB increases, there is significant increase in blood flow to the respiratory muscles and an attendant increase in oxygen consumption.…”
Section: Effect Of Positive Airway Pressure On Lung Function In Acutementioning
confidence: 99%
“…Over the past three decades, application of noninvasive ventilation (NIV) either with continuous positive airway pressure (CPAP) or Bi-level positive airway pressure (Bi-PAP) has been used with the standardized medical treatment as an effective therapeutic approach to treat ACPE [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The goals of NIV use in the treatment of ACPE are to improve oxygenation, reduce the effort of breathing and increase cardiac output and decreased left ventricular preand after-load [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%